2015
DOI: 10.1111/jfpp.12694
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Submerged Fermentation Parameters for Instant Dark Tea Production by E urotium cristatum

Abstract: In this study, green tea extracts was used as material to produce a kind of instant dark tea by Eurotium cristatum via submerged fermentation. Response surface methodology was implemented with desirability function approach for optimization of fermentation parameters of instant dark tea product. The effects of inoculum size (6-12%), liquid-solid ratio (10-20 mL/g) and fermentation time (132-204 h) on mycelia dry weight, redness and turbidity of fermented tea infusion were investigated. The optimum condition wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…A, C). A smaller LSR again resulted in exponential growth of the microorganism but not enough enzyme production and secretion into the broth, whereas a higher LSR led to nutrient shortfalls that limited metabolite production …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A, C). A smaller LSR again resulted in exponential growth of the microorganism but not enough enzyme production and secretion into the broth, whereas a higher LSR led to nutrient shortfalls that limited metabolite production …”
Section: Resultsmentioning
confidence: 99%
“…However, the amount of low‐grade green tea and crop waste (trimmed leaves, tea dust and mature leaves) produced is even greater. These low‐grade green tea and waste products can be used as inexpensive raw materials for the production of fermented dark tea . Mature tea leaves can be fermented into dark tea after inoculation of microorganisms and culture via solid‐state fermentation .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…are associated with the physical and chemical properties of dark tea and its quality. Research has shown that using raw tea to process instant dark tea products with Eurotium cristatum results in good taste, aroma and colour (Lu et al ). In the existing standards for dark tea, the quality of dark tea is judged through sensory evaluation.…”
Section: Introductionmentioning
confidence: 99%